Comprehensive whole metagenomics analysis uncovers microbial community and resistome variability across anthropogenically contaminated soils in urban and suburban areas of Tamil Nadu, India - Vasanthrao, Ramavath; Nidhin, Illathu Kandy; Taj, Zarin; Chattopadhyay, Indranil (Frontiers in Microbiology, 2025)
IntroductionEnvironmental contamination by heavy metals and hydrocarbons significantly impacts microbial diversity and soil functionality.MethodsThis study employs whole-genome metagenome sequencing to analyse microbial compositions, antibiotic resistance genes (ARGs), heavy metal resistance genes (HMRs), and virulence genes (VGs) in soil samples from diverse locations, including gardens, poultry farms, cattle sheds, markets, hospitals, thermal power plants, paper industries, and waste disposal sites.ResultsThe findings indicate that heavy metal concentrations (Pb, Cr, Cd, and Cu) and hydrocarbons (heptadecane, triacontane, docosane, and heneicosane) were positively correlated with several microbial phyla with relatively high abundances in these contaminated sites, such as Actinobacteria, Proteobacteria, Basidiomycota, Ascomycota, Euryarchaeota, and Apicomplexa. The prevalence of multidrug resistance genes, including MexD, MexC, MexE, MexF, MexT, CmeB, MdtB, MdtC, and OprN, was significant, facilitating antibiotic resistance primarily via efflux pump mechanisms (42%), followed by antibiotic inactivation (23%) and changes in antibiotic targets (18%). Virulence genes such as espR, regX3, sigA/rpoV, bap, and sugB were significantly prevalent in contaminated locations, indicating microbial pathogenic potential in polluted ecosystems. The functional gene analysis revealed significant metabolic pathways related to protein metabolism, carbohydrates, amino acids and their derivatives, metabolism, and DNA metabolism, highlighting the microbial adaptation processes engaged in pollution degradation and resource utilisation.DiscussionThis study establishes a clear link between environmental pollution, microbial adaptations, and functional resilience, emphasizing the ecological significance of microbial bio-remediation in shaping targeted remediation strategies and long-term ecological recovery. Understanding these microbial interactions is essential for developing targeted remediation techniques and assessing long-term ecological recovery in contaminated regions.